Pengaruh Pemberian Ekstrak Buah Pare Terhadap Penurunan Kadar Glukosa Darah Pada Mencit (Mus musculus) - Andi Retno Afifah; Sri Wahyu; Sri Wahyuni Gayatri; Indah Lestari Daeng Kanang; Rezky Putri Indarwati Abdullah (Indonesian Journal of Health, 2021)
Diabetes mellitus (DM) refers to a hyperglycemia syndrome due to various causes. Today, many people consume bitter melon as a diabetes drug. Because according to their thinking, its bitter taste can neutralize blood sugar levels. Momordica charantia (Bitter melon) is a plant that is used as a vegetable and in traditional medicine with hypoglycemic fruit activity. Momordica charantia (Bitter melon) contains an insulin-like compound called charantin which has anti-diabetic properties and helps reduce blood sugar levels. This study aims to determine the effect of giving bitter melon extract (Momordica charantia) on reducing blood glucose levels in mice (Mus musculus). The type of research in this study uses a Literature Review with a Narrative Review design. Extract of bitter melon (Momordica charantia) can reduce blood glucose levels in diabetic mice (Mus musculus) with concentrations of 100 mg/kg, 250 mg/kg and 400 mg/kg. Extract of bitter melon (Momordica charantia) with a concentration of 400 mg/kg can reduce blood glucose which is almost equivalent to giving metformin to diabetic mice (Mus musculus). Extract of bitter melon (Momordica charantia) can reduce blood glucose levels in diabetic mice (Mus musculus). However, it is more effective at a dose of 400 mg/kg